2012
DOI: 10.1177/0954411912444073
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behavior and histological organization of the three-layered passive esophagus as a function of topography

Abstract: The zero-stress state of the mucosa-submucosa and two muscle esophageal layers has been delineated, but their multi-axial response has not, because muscle dissection may not leave tubular specimens intact for inflation/extension testing. The histomechanical behavior of the three-layered porcine esophagus was investigated in this study, through light microscopic examination and uniaxial tension, with two-dimensional strain measurement in pairs of orthogonally oriented specimens. The two-dimensional Fung-type st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…This might cause the esophagus damage and failure. Stavropoulou et al [35] studied the failure criteria for mucosa-submucosa and muscle layers of esophagus. The ultimate tensile strength of mucosa-submucosa and muscle layers were reported as 1149 kPa and 425-530 kPa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might cause the esophagus damage and failure. Stavropoulou et al [35] studied the failure criteria for mucosa-submucosa and muscle layers of esophagus. The ultimate tensile strength of mucosa-submucosa and muscle layers were reported as 1149 kPa and 425-530 kPa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Significant research related to the Esophagiome has been published by many interdisciplinary groups; however, much of this mechanics‐ and modeling‐based research has not yet been integrated into the GI clinical sciences, where the greatest potential impact might be realized. The Esophagiome remains in its infancy in a community that is dominated by applied clinicians and biological scientists.…”
Section: The Physiome and The Esophagiomementioning
confidence: 99%
“…27,28,38,77 Similar to other biological vessels, the esophageal wall undergoes large deformations during bolus transport, and esophageal tissue exhibits nonlinear, pseudoelastic, and anisotropic material properties. 28,33,34,78,79 Hence, the mechanical response of the esophagus is typically represented with large deformation models, such as the Fung-type exponential constitutive model 28,33,35,78,80 and anisotropic microstructure-motivated models. 33,52,79,[81][82][83][84] In the Fung model, esophageal layers are treated as anisotropic and homogeneous materials, while, in the microstructure models, esophageal layers are treated as composite materials, characterized by anisotropic behavior with reinforced fibers in specific orientations.…”
Section: Constitutive Models Relevant To the Esophagusmentioning
confidence: 99%
“…Vanags et al [17] studied the mechanical properties of the oesophagus at various ages and anatomic sections through inflation and tensile experiments and concluded that the mechanical properties were related to its microstructure. Sokolis built a series of constitutive models for the different layers of the oesophagus based on inflation‐extension responses, uniaxial tensile behaviours and relevant histological observations; additionally, his group studied the differences between different oesophageal regions in detail and found that the contents of elastin and collagen were the least for thoracic oesophagus [20]. Meanwhile, Lin et al [9, 10] studied the friction behaviours of oesophagus under different normal loads, velocities, and extend directions to simulate the endoscopy and they concluded that the coefficient of friction of the oesophagus increased with increasing sliding velocities and decreased with increasing normal loads.…”
Section: Introductionmentioning
confidence: 99%